The Identification of Escherichia coli Virulence Gene from Diabetic Foot Ulcer (DFU) at the Diabetes Care Home, Bekasi, West Java, Indonesia - Inggraini, Maulin; Anindita, Reza; Ilsan, Noor Andryan; Nurfajriah, Siti (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
One of the complications of diabetes is diabetic foot ulcer (DFU). One of the bacteria that shows a high prevalence in DFU patients is Escherichia coli. The purpose of this study to determine the virulence gene in E.coli isolated from DFU patients at the Bekasi Diabetes Care Home, West Java, Indonesia. Detection of E.coli virulence genes was carried out using the Whole Genome Sequence (WGS) method. Data analysis was carried out descriptively. This study showed the presence of fdeC, fimH, astA, hlyE, hlyF, csgA, and cvaC genes. This study concluded that the fdeC and fimH genes encode protein expression for the formation of colonisation or biofilm, astA, hlyE, and hlyF genes encode the expression of enterotoxin and hemolysin, csgA genes, and cvaC encode the expression of colicin, Curlin, and microcin C bacteriocin.